THE RESPONS ON GROWTH AND YIELD OF OKRA (Abelmoschus Esculentus (L.) Moench) PLANTS USING SUBSTRATE HYDROPONIC SYSTEM IN VARIOUS EC VALUE OF NUTRITION SOLUTIONS AND TYPES OF PLANTING MEDIA - Yogi Adiyasa Febriantara; Ellen Rosyelina Sasmita; Endah Budi Irawati (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2018)
Okra (Abelmoschus esculantus) L. Moench), is an important vegetable that grows in the tropical and sub-tropical parts of the world. Okra plants contain very high nutritional value (at 100 g of young okra fruit containing 35 g of calories, 89.6 g of water, 6.4 g of carbohydrates, 1.9 g of protein, 0.4 g of fat, 1.2 g of fiber, 0 , 7 g of minerals). In Indonesia, okra plants have not been widely cultivated and the cultivation method has not used the right technology, so it is necessary to examine the proper cultivation methods of Okra. This study aims to determine the EC value of the most optimal nutrient solution and the effect of the type of planting media that is best on the growth and yield of okra plants. The research was carried out in plastic houses located in Pondok, Karangbendo, Banguntapan, Bantul, Yogyakarta in May to August 2018. Experiments using polybag with a Complete Randomized Block Design (RAKL) Split Plot two factors were repeated 3 times. The first factor as the main plot is the EC value of nutrient solution (C1: EC value 1.5 mS / cm, C2: EC value 2 mS / cm, C3: EC value 2.5 mS / cm) and the second factor as sub plot is type planting media (M1: Husk charcoal, M2: Sand Malang, M3: Husk charcoal + Cocopeat (1:1). The results showed that there was no interaction between the treatment of giving various EC values of nutrient solution and type of planting media. The treatment of various EC values of nutrient solution and type of planting media significantly affected the parameters of plant height growth, leaf area, root volume, flowering age, stem diameter, parameters of total fruit yield per plant, fresh weight per fruit, total fruit weight per plant, fruit weight per Ha. The treatment of giving EC values of 2.0 mS / cm showed suitable results for the growth and yield of okra plants. The treatment of the type of husk charcoal growing media showed suitable results for the growth and yield of okra plants.Keywords: Okra Plant, Substrate Hydroponic, Planting Media, Solution EC Value